Knowledge and willingness for Eye Donation in Patients attending a Tertiary eye care centre of Nepal (Purbanchal University Health Journal, 2025)
Introduction: Strategies to prevent corneal blindness are likely to be more cost-effective however, visual rehabilitation by corneal transplantation remains a major treatment option for restoring sight in those who already have corneal blindness. Raising the level of public education and willingness on eye donation is an important first step to reduce the shortage.Objective: To assess the knowledge, attitude and willingness of eye donation of patients and their attendants attending the outpatient department of a tertiary eye hospital in Nepal.Method: A total of 1184 respondents were administered a pretested structured questionnaire. The study was done in a tertiary eye care center and respondents were involved after a written informed consent. The Chi-square test was used to determine the factors associated with willingness towards eye donation. Data was analyzed using SPSS version 17.Result: In this study, 31.08% respondents were willing to pledge for eye donation ,there was significant association of willingness to donate eyes among males (66.1%) (p value=0.0036), among respondents below 40 years of age  (73.91%) (p-value= 0.0025), respondents with higher education status  (65.76%) ( p-value= 0.001) and urban population (79.89%) .Perceived reasons among (45.3%) who were not willing to donate were, (58%) need more information regarding eye donation, (7%) thought family may not allow for eye donation and (11%) respondents did not want to donate due to religious disbelief whereas 24% do not want to donate because donation will disfigure the eye. Majority (78.2%) of the respondents have awareness about the eye donation. However, only 32% of the respondents have knowledge about the eye bank. Media played a major role in creating awareness for eye donation.Conclusion: Multipronged innovative strategies should be adopted to increase the awareness regarding eye donation in less educated and rural population.